2005
DOI: 10.1037/0894-4105.19.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Source-Based and Gist-Based False Recognition in Aging and Alzheimer's Disease.

Abstract: This study examined 2 factors contributing to false recognition of semantic associates: errors based on confusion of source and errors based on general similarity information or gist. The authors investigated these errors in patients with Alzheimer's disease (AD), age-matched control participants, and younger adults, focusing on each group's ability to use recollection of source information to suppress false recognition. The authors used a paradigm consisting of both deep and shallow incidental encoding tasks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 59 publications
9
53
0
1
Order By: Relevance
“…Moreover, younger adults make fewer false alarms for repeatedly studied word lists, indicating an enhancement of item specific information; in contrast, older adults show no suppression of false alarms for repeatedly studied lists (Kensinger and Schacter, 1999). These findings are suggestive of a reduced ability to use recollection of the study list to oppose the build-up of gist (Kensinger and Schacter, 1999; Pierce et al, 2005). Similarly, increasing the category size of a studied list, and thus the strength of the gist trace, negatively influences memory accuracy more for older compared to younger adults (Koutstaal and Schacter, 1997; Pidgeon and Morcom, 2014).…”
Section: Mechanisms Of False Memory Formation With Agementioning
confidence: 99%
“…Moreover, younger adults make fewer false alarms for repeatedly studied word lists, indicating an enhancement of item specific information; in contrast, older adults show no suppression of false alarms for repeatedly studied lists (Kensinger and Schacter, 1999). These findings are suggestive of a reduced ability to use recollection of the study list to oppose the build-up of gist (Kensinger and Schacter, 1999; Pierce et al, 2005). Similarly, increasing the category size of a studied list, and thus the strength of the gist trace, negatively influences memory accuracy more for older compared to younger adults (Koutstaal and Schacter, 1997; Pidgeon and Morcom, 2014).…”
Section: Mechanisms Of False Memory Formation With Agementioning
confidence: 99%
“…These results thus suggest that Alzheimer's patients have difficulties in suppressing false recognition of semantic associates using recollection. Pierce et al [55] used a different paradigm, originally proposed by Smith et al [56] in which recollection of source information is needed to avoid intruding presented exemplars from categorized lists. Alzheimer's patients were unable to use recollection to avoid intrusions.…”
Section: Memory For Both Gist and Detail Information Decreases Inmentioning
confidence: 99%
“…Specifically, it is well established that recall tasks are reliable predictors of transitions to AD among older adults (for reviews, see Petersen et al, 1999;Spaan et al, 2004), and more recently, it has been found that the predictive power of recall tasks increases when they stress semantic processing (e.g., Benedict, Schretlen, Groninger, & Brandt, 1998). This has prompted the hypothesis that a hallmark of transition to AD is increasing difficulties with semantic processing (e.g., Budson et al, 2002Budson et al, , 2003Pierce, Sullivan, Schacter, & Budson, 2005;Reyna & Mills, 2007). Under that hypothesis, reconstruction parameters ought to have lower values in AD patients than in healthy older adults because those parameters measure the processing of items' semantic content (Reyna & Mills, 2007).…”
Section: Fixed-trials Implementation Comparisons Of Healthy and Impaimentioning
confidence: 99%